Risk factors associated with low back pain in competitive female gymnasts: A meta-analytic approach. Issue 22 (16th November 2020) - Cugusi, Lucia; Manca, Andrea; Sarritzu, Sara; Bergamin, Marco; Gobbo, Stefano; Di Blasio, Andrea; Massidda, Myosotis; Cupisti, Adamasco; Bandiera, Pasquale; Deriu, Franca
ABSTRACT: The aim of this meta-analysis was to aggregate data from studies investigating the risk factors associated with low back pain (LBP) in competitive gymnasts. Four databases were searched and studies reporting demographics, anthropometrics, functional, psychosocial and gymnastics-practice variables in competitive gymnasts with and without LBP were included. For continuous data, the weighted mean difference (MD) and confidence interval (95% CI) were calculated, while odds or risk ratio (OR, RR) were calculated for dichotomous data. Meta-analysis of six cross-sectional studies involving 284 competitive female gymnasts revealed that artistic were more likely to report LBP compared to rhythmic gymnasts (RR 1.4, 95% CI 1.04–2.0, Z=2.2, p= 0.03). Data pooling revealed that age (MD 1.5 years, 95% CI 0.4–2.5, p =0.005) and body weight (MD 3.5 kg, 95% CI 0.1–6.8, p =0.04) were significantly higher in gymnasts with LBP compared to those without. Subgroup-analyses confirmed these differences in artistic but not in rhythmic gymnasts. Moreover, artistic gymnasts with LBP tended to display longer gymnastics-practice history ( p= 0.09) compared to those without. Increased age, body weight and, to a lesser extent, longer gymnastics-practice appear to differentiate artistic gymnasts with LBP from those without; conversely, these potential risk factors seem less relevant for rhythmic gymnasts.